Analysis of Amino Acid Profiles in Bone, Oil, and Muscle Tissue and Wound Healing Activity of Pangasius hypophthalmus Oil in Rattus norvegicus - Hidayaturrahmah, Hidayaturrahmah; Suprayogi, Agik; Hanif, Novriyandi; Roosita, Katrin; Darusman, Huda Shalahudin; Aprilyana, Lia (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Patin (Pangasius hypophthalmus), a commercially important freshwater fish, is a rich source of protein containing both essential and non-essential amino acids, crucial for various biological functions. This study aimed to determine the amino acid composition of muscle tissue, oil, and bones of P. hypophthalmus and evaluate the wound healing potential of its oil extract in Rattus norvegicus. High-Performance Liquid Chromatography was employed to quantify the levels of essential and non-essential amino acids in each tissue. Results revealed that P. hypophthalmus oil exhibited the highest total amino acid content, particularly rich in histidine, arginine, and lysine. The wound healing activity of P. hypophthalmus oil extract was assessed in a rodent model, demonstrating a significant reduction in wound area (0.62-0.84 mm) and an impressive wound healing percentage (79-84.45%). These findings suggest that different parts of P. hypophthalmus possess valuable nutritional and therapeutic properties. Notably, the high amino acid content of P. hypophthalmus oil, particularly essential amino acids, highlights its potential as a promising source for developing pharmaceutical products, including amino acid supplements, wound healing agents, and formulations for metabolic support. Further research is warranted to fully explore the therapeutic potential of P. hypophthalmus oil and its bioactive components.